Reduced graphene oxide/gold nanoparticles based ultrasensitive resistive sensor for PCA3 - Shivam Kumar; Nikita Bhandari; Sudhanshu Shukla; Ruma Ghosh (Biosensors and Bioelectronics: X, 2024)
Early prostate cancer detection can be improved by detecting more specific markers like PCA3 RNA. This study reports a novel and simple method for detecting PCA3 RNA using a sensor based on reduced graphene oxide (RGO), gold nanoparticles (AuNP), and a single-stranded DNA (ssDNA). The device was characterized at each fabrication step using atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The RGO/AuNP/ssDNA sensor exhibited a significant change in resistance (6.51–15.01%) when exposed to varying concentrations of PCA3 (0.1–100 ng/mL). The developed device showed selective response towards PCA3 (14.5% for 50 ng/mL) when compared with negative controls like phosphate buffer saline solution (0.28%), PCA3-negative control sample (1.03%), RNA extracted from lung cancer (0.88%), and breast cancer (1.17%) cell lines. The RGO/AuNP/ssDNA sensor could also be employed to quantify the PCA3 RNA present in the RNA mixture extracted from a prostate cancer cell line and the observed findings were in excellent agreement with semi-quantitative real-time polymerase chain reaction (RT-PCR) results.